Performance, combustion and emission characteristics of the CI engine fueled with Botryococcus braunii microalgae with addition of TiO2 nanoparticle. (1st June 2022) - Ge, Shengbo; Brindhadevi, Kathirvel; Xia, Changlei; Salah Khalifa, Amany; Elfasakhany, Ashraf; Unpaprom, Yuwalee; Whangchai, Kanda
Highlights: Botryococcusbraunii microalgae blends tested in the conventional diesel engines for the sustainability. Effects of TiO2 examined for performance and emission characteristics. 20% microalgae generate higher brake thermal efficiency compared to neat blends. Emission of HC, CO and CO2 were dropped massively due to the influence of nanoparticles. Abstract: Production of biofuels from the green synthesis considered to be the promising source of the energy to replace the conventional fuels. Further the usage of the biofuels in the optimized ratio will effectively reduce the environmental concerns and the reduce the greenhouse gas emission. In this study, the impact of the Botryococcus braunii microalgae along with the diesel was examined. From the previous work it is understood that, usage of the Botryococcus braunii in the diesel affects the combustion and performance characteristics. To avoid the shortcomings, the nanoparticles TiO2 (50 ppm) were dispersed in the biodiesel blends by sonication method. The test blends such as D100 (100% diesel), B100 (neat microalgae oil), B10 (20% microalgae + 80% diesel), B10T (20% microalgae + 80% diesel), B30 (30% microalgae + 70% diesel) and B30 (30% microalgae + 70% diesel) were tested at engine loads of 0%, 25%, 50%, 75% and 100%. Individual blends were tested for brake thermal efficiency, brake specific fuel consumption, indicated thermal efficient, cylinder pressure and emission of NO, HC, CO and CO2 . Based on the findings, addition of the microalgae blends with the nanoparticles enhances the BTE by 5% and 3% for BT20 and BT30, respectively, compared to neat diesel. Further, the BSFC was precisely reduced for B30 compared to D100 and B20 due to the viscosity of the blends. The role of the mixed fuel addition along with nanoparticles increases the cylinder pressure and heat release rate. With regard to emission, the CO, HC and CO2 reported significant drop in the emissions. However, NOx emissions remain to be high despite the engine speed for the blends B30.